2017
DOI: 10.2140/memocs.2017.5.41
|View full text |Cite
|
Sign up to set email alerts
|

On the possible effective elasticity tensors of 2-dimensional and 3-dimensional printed materials

Abstract: The set GU f of possible effective elastic tensors of composites built from two materials with elasticity tensors C1 > 0 and C2 = 0 comprising the set U = {C1, C2} and mixed in proportions f and 1−f is partly characterized. The material with tensor C2 = 0 corresponds to a material which is void. (For technical reasons C2 is actually taken to be nonzero and we take the limit C2 → 0). Specifically, recalling that GU f is completely characterized through minimums of sums of energies, involving a set of applied st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 91 publications
1
55
0
Order By: Relevance
“…Figure 7(C) indicates that limit laminate structures also remain very close to Hashin-Shtrikman bound for volume fractions smaller than 1 (see also Figure 10). These results are consistent with the ones obtained previously in [26] and recent work [18], establishing the attainability of the right Hashin-Shtrikman bound for volume fractions smaller than 1.…”
Section: Numerical Studiessupporting
confidence: 93%
“…Figure 7(C) indicates that limit laminate structures also remain very close to Hashin-Shtrikman bound for volume fractions smaller than 1 (see also Figure 10). These results are consistent with the ones obtained previously in [26] and recent work [18], establishing the attainability of the right Hashin-Shtrikman bound for volume fractions smaller than 1.…”
Section: Numerical Studiessupporting
confidence: 93%
“…We have shown that our metastructures are not subject to this restriction and can generate low-frequency band gaps even if the end diameter of inclined bars is larger than the central one. Further interesting possibilities can be envisioned for future extensions to recently proposed 'rank 2' and 'rank 3' walled structures [40]. Table A1.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of the investigations was more specifically (1) to design novel and exotic architectured metamaterials based on a mathematical understanding of the related mechanical problems and on suitably designed numerical simulations, (2) to build the designed prototypes by using 3D printing technology, (3) to test with sensitive apparatuses the so-built prototypes, (4) to elaborate the obtained data with modern image correlation techniques, (5) to produce a careful model fitting of the experimental data by means of the systematic use of numerical simulations, and (6) to compare the proposed models with experimental evidence.…”
Section: Introductionmentioning
confidence: 99%
“…With the latest advancements (e.g., 3D-printing technology and, more generally, of rapid prototyping techniques), the small-scale production of materials with complex geometries has become more affordable than ever [1][2][3][4]. The exploitation of these new technologies has made possible the development in the last few years of materials with very different substructures.…”
Section: Introductionmentioning
confidence: 99%